Role of projectile charge state in convoy electron emission by fast protons colliding with LiF(0 0 1) - Aldazabal, I. (2005)
Target ionization and projectile ionization differential cross sections are used to calculate the electron emission spectra by fast proton impact on ionic crystal surfaces under grazing incidence conditions. Both bare protons and neutral hydrogen species are considered. We use a planar potential approach to determine the projectile trajectory that later on allows us to calculate the charge state fractions. We show that, although the fraction of protons is significantly higher, the contribution from neutral hydrogen ionization has to be considered. The energy and angular dependence of the spectra is analyzed.